Pembuatan Aplikasi Jual Beli Makanan Berbasis Android - Denny Yosowanto; Leo Willyanto Santoso; Agustinus Noertjahyana (Jurnal Infra, 2017)
Currently, the development of technology has greatly advanced. With the development of technology, it can help people become more effective and more efficient. Business selling food is becoming a trend in all circles. It can be seen from the many social media accounts selling food online and offline. Location sellers dishes that sometimes being away from the residence buyer makes the buyer difficult to buy food. Associated with the development of technology and the business of buying and selling food is the current trend of buying and selling food made application that aims to facilitate the consumers to get the desired food effectively and efficiently. This application has four main parts: the buyer, the seller, courier, and admin. Features contained in this application is that users can register themselves online through the app, sellers can upload foods to be sold via the menu on the seller, the buyer can order culinary menu available through vendors who joined in the application, and courier mediates between the seller and the buyer so the buyer can get the buyer's order with ease. This application uses the Google API to get the seller's location closest to the buyer, calculate postage based on the distance between sellers and buyers, and to give directions so that the courier service can deliver orders from the seller to the buyer to make it easier.Overall, the application can run well. This application can be expected to mediate between lovers the Surabaya to enjoy the culinary menus from various sellers in Surabaya both restaurants, street food, the food online shop, food home industries.